Pengaruh Penggunaan Media Youtube dan Kualitas Produk Terhadap Brand Awareness Gitar Elektrik Pada Konsumen CV Sang Adi Musik Indonesia Di Mojokerto - Chusnul Chotimah; Nur Hidayati; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of using Youtube media and product quality on brand awareness of electric guitars among consumers of CV Sang Adi Musik Indonesia. The sampling technique used was purposive sampling so that a sample of 70 data was obtained. This study uses primary data using a questionnaire as a data collection method, validity test used as a data analysis technique, reliability test, normality test, multiple linear regression, and t test, with IBM Spss V-20 tools. The results showed that the use of Youtube Media and Product Quality simultaneously had a positive and significant effect on Brand Awareness. Partially, the use of Youtube media has a positive and significant effect on brand awareness, product quality has a positive and significant effect on Brand awareness. Keywords: Youtube Media, Product Quality, Brand Awareness.